Pattern of skin diseases seen in the dermatology clinic of Rivers State University Teaching Hospital, Port Harcourt, Nigeria - Amaewhule, Mary N. (International Journal of Research in Dermatology, 2025)
Background: Skin diseases are a source of significant health concern worldwide. Understanding its epidemiology is important for effective healthcare planning. In our hospital, this study is the first of its kind. This study examines the pattern and trends of skin diseases as seen in RSUTH. Methods: Medical records of patients seen in the dermatology clinic of RSUTH between August 2020 and August 2021 were retrieved, recorded and analyzed with SPSS version 27. Results: The total number of patients seen during this period was 294. However, 4 were excluded due to insufficient data leaving 290 persons. Of these, 189 were females, while 101 were males. Age range is between 6 months and 88 years Mean age is 31.6692±16.87406. Commonest group of skin disorders is infectious skin diseases, commonest diagnosis is Dermatophytosis followed by Acne vulgaris. The least diagnosed disorders are nail disorders and autoimmune disorders. Conclusions: A wide variety of skin diseases were seen in the subjects during the period of study. Dermatophytosis was the commonest skin disease seen while nail disorders was the least prevalent.